Empowerment of KWT Roay Lestari through Drip Irrigation, Digital Marketing and Harvest Processing - Taufik, Nuryanti; Rahayuningrat, Prahita Sri; Mutmainah, Lu'liyatul; Andani, Listia; Fikrinnisa, Rizka; Rasyid, Ari Farizal (FEBI UIN Sunan Kalijaga Yogyakarta, 2025)
Women Farmers Group (KWT) plays an important role in supporting the progress of the agricultural sector. KWT Roay Lestari is a farmer women's group in Kahuripan Village, Tawang Subdistrict. KWT Roay Lestari focuses on processing and marketing processed agricultural products. However, limited resources and knowledge hinder the optimization of KWT's role. This empowerment aims to improve the welfare of KWT through better processing and marketing of farm products. The holistic approach to implementing empowerment includes skills development, working capital support, and marketing capacity building. Based on the results of the activities, a positive impact was obtained through increased skills and independence of KWT members in product processing and marketing. This program can be a replicated empowerment model in other areas to encourage food security and community economic welfare.